PENGELOLAAN WAKAF DI JORONG TIGO BATUR NAGARI SUNGAI TARAB KECAMATAN SUNGAI TARAB - Widi Nopiardo (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Waqf does not only have a dimension of worship, but also has a social dimension because it has a broad impact on strengthening economic resilience. The purpose of this study was to describe the management of waqf in one area in Tanah Datar District, precisely in Jorong Tigo Batur Nagari Sungai Tarab, Sungai Tarab District. The results showed that waqf managers here had tried to implement waqf management well, Nazhir Wakaf, mosque administrators, and the community synergized in the management of the waqf assets. Management of waqf in the Tigo Batur area in the form of building multi-purpose buildings, mosques and productive waqf in the form of rice fields. Endowments in the form of rice fields implement a system for hagi results between the mosque and the people who manage it. The management of the paddy fields was fully handed over to the community, aiming to improve the welfare of the people of Jorong Tigo Batur. Nadzir Wakaf experienced obstacles in developing waqf for productive programs such as hospital construction, super market development, and so on, so that this program could not be realized.